Why blog? : motivations for blogging - Pedersen, Sarah (Professor of communication and media) (Chandos information professional series., 2010)
'Weblogging' or 'blogging' has joined e-mail and Internet home pages as one of the most popular uses of the Internet. This book focuses on the British blogosphere, comparing British bloggers to the more researched US. Motivations covered include the desire to connect with others online, the need to express opinions or blow off steam, or to share experiences, and a growing financial motivation in the blogosphere. Other motivations explored include a desire to become a 'citizen journalist', a need for validation, the commercial possibilities of blogging and the possibility of turning your blog into a published 'book'. Expands the discussion of the blogging phenomenon outside the USFocuses on the British blogosphere, comparing British bloggers to the more researched USIncludes a discussion of the motivations of women bloggers.